( | 4 | x | − | 1 | ) | ÷ | 3 | − | ( | x | − | 1 | ) | ÷ | 2 | = | 2 |
方程左边 = | 4 | x | × | 1 3 | − | 1 | × | 1 3 | − | ( | x | − | 1 | ) | × | 1 2 |
= | 4 3 | x | − | 1 3 | − | ( | x | − | 1 | ) | × | 1 2 |
= | 4 3 | x | − | 1 3 | − | x | × | 1 2 | + | 1 | × | 1 2 |
= | 4 3 | x | − | 1 3 | − | x | × | 1 2 | + | 1 2 |
= | 5 6 | x | + | 1 6 |
5 6 | x | + | 1 6 | = | 2 |
5 6 | x | = | 2 | − | 1 6 |
5 6 | x | = | 11 6 |
x | = | 11 6 | ÷ | 5 6 |
= | 11 6 | × | 6 5 |
= | 11 | × | 1 5 |
x | = | 11 5 |
x | = | 2.2 |